Numerical simulations of gas mixing effect in electron cyclotron resonance ion sources - V. Mironov; S. Bogomolov; A. Bondarchenko; A. Efremov; V. Loginov (Physical Review Accelerators and Beams, 2017)
The particle-in-cell Monte Carlo collisions code nam-ecris is used to simulate the electron cyclotron resonance ion source (ECRIS) plasma sustained in a mixture of Kr with O_{2}, N_{2}, Ar, Ne, and He. The model assumes that ions are electrostatically confined in the ECR zone by a dip in the plasma potential. A gain in the extracted krypton ion currents is seen for the highest charge states; the gain is maximized when oxygen is used as a mixing gas. The special feature of oxygen is that most of the singly charged oxygen ions are produced after the dissociative ionization of oxygen molecules with a large kinetic energy release of around 5 eV per ion. The increased loss rate of energetic lowly charged ions of the mixing element requires a building up of the retarding potential barrier close to the ECR surface to equilibrate electron and ion losses out of the plasma. In the mixed plasmas, the barrier value is large (∼1  V) compared to pure Kr plasma (∼0.01  V), with longer confinement times of krypton ions and with much higher ion temperatures. The temperature of the krypton ions is increased because of extra heating by the energetic oxygen ions and a longer time of ion confinement. In calculations, a drop of the highly charged ion currents of lighter elements is observed when adding small fluxes of krypton into the source. This drop is caused by the accumulation of the krypton ions inside plasma, which decreases the electron and ion confinement times.